Adsorption of methyl green stain from aqueous solutions using non-conventional adsorbent media: Isothermal kinetic and thermodynamic studies. (June 2021) - Alalwan, Hayder A.; Mohammed, Malik M.; Sultan, Abbas J.; Abbas, Mohammed N.; Ibrahim, Thekra A.; Aljaafari, Haydar A.S.; Alminshid, Alaa A.
Abstract: Eggshell waste which is a serious issue that faces the authorities of food industries was used to adsorb methyl green stain from aqueous solutions. The impact of pH solution of several parameters on the removal efficiency was investigated. The results show that the maximum percent of removal was 69.38 ± 3% and it was directly proportional with pH, agitation speed, adsorbent dose, and contact time. While the relation with temperature and initial concentration was inverse. The isotherm, kinetic and thermodynamic studies were also done under the system optimum conditions. The results show that the pseudo-second order kinetic model and Langmuir isotherm model are the best models that describe the adsorption system, while the thermodynamic investigation illustrates that the removal process was endothermic, spontaneous, and less entropic. This work provides detailed information about an innovative method to utilize eggshell waste as an inexpensive adsorbent to remove methyl green stain from aqueous solutions. Graphical abstract: Unlabelled Image Highlights: Eggshell powder is a promising unexpensive adsorption material. Utilizing eggshell as adsorbent material is a solution for eggshell disposal issue. The physisorption process has a removal efficiency of 69.38% at optimum conditions. The process follows the pseudo-second order kinetic and Langmuir isotherm models. Adsorption process is spontaneous, endothermic, and less entropic.